Comparative Assessment of Architects and Manufacturers Behaviors for Obtaining and Presenting Environmental in formation of Building Products in Turkey - Serter, Nursah; Tuna Taygun, Gokce (Yildiz Technical Univ, Fac Architecture, 2020)
The construction sector, and therefore also the vast majority of building products, consume finite resources and affect the environment throughout their life cycle. As part of the effort to address environmental problems that originate from building products, manufacturers are now expected to declare the environmental impact of their products and architects who make product decisions should take the responsibility of choosing those products that have the least impact on the environment. Preliminary studies of a system to collect information about building products have been ongoing in Turkey since the early 2000s. However, these studies include mostly technical information and cost-oriented details. There is still a need for an information system that provides information about the environmental impact of these products to help guide responsible decision-making. The objective of this study was to examine the methods used to choose building materials and compare the environmental characteristics of the products using a comprehensive examination and prepared surveys. The results will provide data for the design of the Environmental Information System for Building Products (EISBP), a single source of detailed information about these products. The environmental impact characteristics of the materials that architects and building product manufacturers valued, and the preference and activity trends of these two stakeholders of the Turkish construction industry were evaluated using surveys of independently selected respondents to determine the environmental features of the products, the ways in which that information was obtained and presented, and the product decision criteria. One survey was sent by e-mail to architects who have an office registered with the Chamber of Architects in the Marmara Region. A second survey was conducted in face-to-face interviews with construction product representatives at a building and construction trade show. The responses of the two samples to the same questions were examined. A t-test was used to analyze the study data. The preferences and priorities of the two stakeholder groups with regard to the environmental characteristics of building products, the importance given to that information, and other environmental decisions and comparisons were analyzed and evaluated. The decision-makers surveyed were architects registered with the Chamber of Architects in the Marmara Region and manufacturers of paint,joinery, wall, flooring and roofing materials participating in a building fair. The results revealed that both the representatives of the manufacturers and the architects primarily relied on manufacturer websites as sources of information for product decisions and promotion. Architects next turned to online catalogs where they can view and compare products. The manufacturers' representatives indicated that they tended to use printed brochures as a secondary source of product promotion. It is noteworthy that the most important feature for architects was a product guarantee. Naturally, both groups cared most about the performance characteristics of a product. When the responses of the two groups regarding the decision criteria for environmentally friendly building products were examined, it was observed that information about the life cycle of the products was considered important. It would appear that the environmental awareness of both groups of stakeholders working in the Turkish construction sector has increased in recent years. The demand for environmental information about building products reinforces the necessity for the EISBP. The study also provides suggestions for environmentally friendly product decision criteria to be used in the design of the EISBP as well as suggestions for a web-based EISBP interface. Easily accessible information can assist with better product decision-making, which will help to decrease environmental problems originating from construction and building products.
Türkiye’de Mimarlar ve Üreticilerin Yapı Ürünlerinin Çevresel Bilgilerini Elde Etme ve Sunma Davranışlarının Karşılaştırmalı Olarak Değerlendirilmesi
Keywords: Building product; environmental characteristics in product decision; environmental impact details of building products; product information system; product life cycle